A review on the classification and current treatment of Chronic Kidney Disease - Żuberek, Michał; Popińska, Zuzanna; Ślusarczyk, Daniel; Żmuda, Bartłomiej; Jakubowska, Wiktoria; Pisera, Piotr; Kiełkowicz, Aleksandra; Pactwa, Filip (Journal of Education, Health and Sport, 2023)
Introduction: Chronic Kidney Disease (CKD) is a chronic condition which is characterized by the gradual loss of kidney function over time leading to End-Stage Renal Disease (ESRD). Role of kidneys is very vital to maintain homeostasis of the system. CKD is classified into five stages based on the estimated Glomerular Filtration Rate (eGFR). CKD is a long-term condition which cannot be completely cured. Treatment focuses on managing underlying conditions , slowing disease progression and addressing complications. Aim of the study: Purpose of this study is to encapsulate available knowledge about classification and therapeutic options for patients with Chronic Kidney Disease and End-Stage Kidney Disease. Both old and new treatment methods have been summarized in the following publication. Material and methods: Literature available in the PubMed database was reviewed using the following keywords: “Chronic kidney disease”, “ACE inhibitors” , “Angiotensin II Type 1 Receptor Blockers", “Diabetic Kidney Disease” ,”End-Stage Kidney Disease”, “Dapagliflozin”, Conclusions: Chronic Kidney Disease is a condition which is progressive and affects more than 10% of the general population worldwide totaling over 800 million people. There are many causes of chronic kidney disease; therefore, it is important to focus on slowing the progression of the disease, minimizing complications and modifying risk factors.